Model Pembelajaran Aktif Pada Pembelajaran Pendidikan Agama Islam Dalam Buku Metodologi Pendidikan Agama Islam Karya Ramayulis - Rahman, M. Dwi Rahman Sahbana (UIN Sulthan Thaha Saifuddin Jambi, 2024)
This research aimed at finding out how active learning model was on Islamic Education learning in the book of Metodologi Pendidikan Agama Islam created by Ramayulis. It was a library research. The technique of collecting data was documentation study. The method of analyzing data was content analysis related to the content contained in the book of Metodologi Pendidikan Agama Islam. Content analysis was carried out by classifying, analyzing, and describing the analysis results. Based on the research findings, it could be concluded that active learning model on Islamic Education learning in the book of Metodologi Pendidikan Agama Islam created by Ramayulis was a pattern that could be used to form a curriculum (long-term lesson plan) and design learning materials in the classroom or another. The goal was to develop active learning in the classroom. Its function was as a step for the teachers to realize an active Islamic Education learning process. There are two active learning models that could be implemented today—Contextual Teaching and Learning (CTL) learning model, Web-based learning model (E-Learning).